Psychological capital, affective commitment, and citizenship behavior: PLS-SEM modelling approach - Shakil, Rashed Mahmud (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
Psychological capital (PC) has become critical to positive workplace outcomes, including supporting organizational citizenship behavior (OCB). This research explores the relationships between PC and OCB with the mediating role of affective commitment (AC) as contextualized in Bangladeshi small and medium-sized enterprises (SMEs). A total of 200 full-time employees working in different SMEs of Bangladesh are included in the study, based on a purposive sampling method. Drawing on variance-based structural equation modelling (SEM), the research examines how psychological resources (optimism, resilience, hope, and self-efficacy) facilitate employees’ discretionary efforts to achieve organizational goals. The results identify AC as an important mediation mechanism through which strong emotional attachment in employees can transform psychological capital into OCB. The research contributes critically to theoretical development and offers actionable implications for practice by providing empirical insights into the mediating role of AC in the PC-OCB relationship. The managers and entrepreneurs can promote PC through relevant training and a supportive environment that increases the employees' commitment and leads them to perform behaviors beyond the demands of their formal role. Consequently, this study emphasizes the roles of psychological capital and affective commitment in developing an organizational citizenship culture critical to the long-term success of SMEs in Bangladesh